Resolution of acanthosis nigricans following curative gastric carcinoma resection - Jagwani A.V.; Reynu R.; bin Affirul A.C.; Mustafa M.T.; Kosai N.R. (Societa Editrice Universo, 2024)
Indexed by WOS/ Scopus